Extent of Allergens in Patients with Chronic Contact Dermatitis Using Patch Test in Tripoli, Libya - Aisha El-ashouri; Laila Sabei; Hamida Aldwebi; Amr Azeem (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and aims. Occupational contact dermatitis (OCD) is one of the most common work-related cutaneous disorders in many countries. The long-term prognosis of the patients with chronic contact dermatitis (CCD) is poor, involving low health-related quality of life and negative occupational consequences. Our study was aimed to determine the common sensitizing allergens lead to allergic contact dermatitis (ACD) by using TRUE patch test (PT) and to evaluate them according to the age, sex and occupation. Methods. Eighty-seven patients with CCD were tested using TRUE PT Test after applied inclusion and exclusion criteria. Results. The most frequent detected allergen was potassium dichromate (PDC) (21.8%), and was significantly more than the other metals (P=0.022), followed by cobalt chloride (CC) (9%), and nickel sulfate (NS) (6.8%). The cleaning services including housewives (HW) considered the common occupation in our cases with metal contact dermatitis (41.6%) (P = 0.865), and 33% of them had allergic reaction to more than one metal, where 25% were significantly allergic to both PDC and CC (P = .044). Conclusion: Study concludes that metals were the most frequent allergens lead to ACD among cleaning services including HW and PDC was the most frequent.